Negro Folksong Scholarship in the United States - Thieme, Darius L. (International Library of African Music, 1960)
The purpose of this article will be to serve as a bibliographical aid—to refer the reader to some of the standard reference works, bibliographies and finding aids, to name a few of the many collectors in this field, to cite some of the archives which contain pertinent material, and to list some of the more recent books and articles. Research on this subject will be surveyed under several subheadings (see below). These subheadings are chosen purely for the writer’s convenience, although at the same time they may be taken as indicating some of the related research fields which contribute to our understanding of the overall topic.
Keywords: Research; Music; African Americans; Ethnomusicology; Folklore; African Music